THE IMPLEMENTATION OF FINANCIAL MANAGEMENT AT PT. MYKANTA - Rumagit, Anastasia Bonitha; Tielung, Maria V. J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Financial Management is useful for regulating the capital and the company money to be used efficiently, as effective and productive as possible in order to earn profit. Financial management is the way of the company to control the company's activities from planning to evaluation and reporting. In the application of financial management there are seven principles that must be applied by the company. The seven principles are consistent, accountability, transparency, viability, integrity, stewardship and accounting standard. Those principles can be directed in a way to implement financial management. This research is using qualitative method that will describe the topic and explain the result of the interview. The object of the research is PT. Mykanta as contractor company in Manado. The purpose of this research is to know how the implementation of financial management in contractor company, whether the company already meets the seven principles that become the standard for financial management. The result of the research is that the PT. Mykanta already implementing the financial management, but this company must improve it with the addition of the employee to support the company's activities. Management company should pay attention anymore financial management in order to run properly, as effective and efficient as possible. A company will not develop if one field is problematic or not managed properly. Keywords: financial management, consistent, accountability, transparency